Economic Costs of Providing District- and Regional-Level Surgeries in Tanzania - Martilord Ifeanyichi; Henk Broekhuizen; Adinan Juma; Kondo Chilonga; Edward Kataika; Jakub Gajewski; Ruairi Brugha; Leon Bijlmakers (Kerman University of Medical Sciences, 2022)
Background Access to surgical care is poor in Tanzania. The country is at the implementation stage of its first National Surgical, Obstetric, and Anesthesia Plan (NSOAP; 2018-2025) aiming to scale up surgery. This study aimed to calculate the costs of providing surgical care at the district and regional hospitals.Methods Two district hospitals (DHs) and the regional referral hospital (RH) in Arusha region were selected. All the staff, buildings, equipment, and medical and non-medical supplies deployed in running the hospitals over a 12 month period were identified and quantified from interviews and hospital records. Using a combination of step-down costing (SDC) and activity-based costing (ABC), all costs attributed to surgeries were established and then distributed over the individual types of surgeries. These costs were delineated into pre-operative, intra-operative, and post-operative components.  ResultsThe total annual costs of running the clinical cost centres ranged from $567k at Oltrumet DH to $3453k at Mt Meru RH. The total costs of surgeries ranged from $79k to $813k; amounting to 12%-22% of the total costs of running the hospitals. At least 70% of the costs were salaries. Unit costs and relative shares of capital costs were generally higher at the DHs. Two-thirds of all the procedures incurred at least 60% of their costs in the theatre. Open reduction and internal fixation (ORIF) performed at the regional hospital was cheaper ($618) than surgical debridement (plus conservative treatment) due to prolonged post-operative inpatient care associated with the latter ($1177), but was performed infrequently due mostly to unavailability of implants.Conclusion Lower unit costs and shares of capital costs at the RH reflect an advantage of economies of scale and scope at the RH, and a possible underutilization of capacity at the DHs. Greater efficiencies make a case for concentration and scale-up of surgical services at the RHs, but there is a stronger case for scaling up district-level surgeries, not only for equitable access to services, but also to drive down unit costs there, and free up RH resources for more complex cases such as ORIF.